Gender differences in cardiology: is it time for new guidelines?. Issue 12 (December 2018) - Sciomer, Susanna; Moscucci, Federica; Dessalvi, Christian Cadeddu; Deidda, Martino; Mercuro, Giuseppe
Abstract : N/A: Despite cardiovascular disease (CVD) now being the leading cause of morbidity and mortality in women worldwide, this problem is still dramatically underestimated. The disparities in diagnosis, treatment, and prognosis between men and women are rooted in basic biological differences, as well as in the complex interactions of cultural and socioeconomic problems. This is why an up-to-date and gender-based revision of current guidelines is highly desirable.